REGULATION AND THE SOCIAL IMPACT OF P2P LENDING FINTECH: A STUDY OF CONSUMER PROTECTION IN ILLEGAL ONLINE LENDING IN INDONESIA - Gunawan Widjaja (Adisam Publisher, 2026)
The proliferation of illegal online lending (pinjol) in Indonesia has triggered a serious socio-economic and humanitarian crisis, despite the regulatory framework for fintech peer-to-peer (P2P) lending having been strengthened through Financial Services Authority (OJK) Regulation No. 40 of 2024. This article aims to examine two main dimensions: first, the effectiveness of regulations and consumer protection mechanisms within the fintech P2P lending ecosystem; second, the multidimensional social impacts caused by illegal online lending on individuals, families, and Indonesian society. This study employs a literature review (library research) using a descriptive-analytical qualitative approach. The findings indicate that whilst Indonesia’s regulatory framework is comprehensive in theory, its effectiveness is hampered by cross-border jurisdictional gaps, low levels of digital financial literacy among the public (only 38 per cent), and limited law enforcement capacity. The social impact of illegal online lending has gone beyond material losses and transformed into a humanitarian crisis encompassing severe psychological distress (68% of victims suffer from chronic depression and anxiety), the destruction of social relationships due to the practice of personal data dissemination (doxing), exponential debt cycles that cripple household economies, and even suicides that claim lives. This phenomenon also erodes social capital, deepens structural inequality, and undermines public trust in state institutions. This article recommends a holistic approach that integrates the strengthening of cross-border law enforcement cooperation, the acceleration of transformative digital financial literacy, the establishment of compensation and psychosocial rehabilitation mechanisms for victims, and structural reforms to expand access to formal financial services as a long-term preventive solution. Without such comprehensive intervention, P2P lending fintech innovations risk becoming a double-edged sword that widens social injustice and hinders Indonesia’s inclusive and sustainable digital economic transformation.